Metabolic Engineering To Produce Tyrosine or Phenylalanine in a Tryptophan-Producing Corynebacterium glutamicum Strain - Ikeda, Masato (1992)
The aromatic amino acids are synthesized via a common biosynthetic pathway. A tryptophan-producing mutant of Corynebacterium glutamicum was genetically engineered to produce tyrosine or phenylalanine in abundance. To achieve this, three biosynthetic genes encoding the first enzyme in the common pathway, 3-deoxy-d-arabino-heptulosonate 7-phosphate synthase (DS), and the branch-point enzymes chorismate mutase and prephenate dehydratase were individually cloned from regulatory mutants of C. glutamicum which have either of the corresponding enzymes desensitized to end product inhibition. These cloned genes were assembled one after another onto a multicopy vector of C. glutamicum to yield two recombinant plasmids. One plasmid, designated pKY1, contains the DS and chorismate mutase genes, and the other, designated pKF1, contains all three biosynthetic genes. The enzymes specified by both plasmids were simultaneously overexpressed approximately sevenfold relative to the chromosomally encoded enzymes in a C. glutamicum strain. When transformed with pKY1 or pKF1, tryptophan-producing C. glutamicum KY10865, with the ability to produce 18 g of tryptophan per liter, was altered to produce a large amount of tyrosine (26 g/liter) or phenylalanine (28 g/liter), respectively, because the accelerated carbon flow through the common pathway was redirected to tyrosine or phenylalanine.